2008
DOI: 10.1128/ec.00330-07
|View full text |Cite
|
Sign up to set email alerts
|

Increased Respiration in the sch9Δ Mutant Is Required for Increasing Chronological Life Span but Not Replicative Life Span

Abstract: Loss of the protein kinase Sch9p increases both the chronological life span (CLS) and the replicative life span (RLS) of Saccharomyces cerevisiae by mimicking calorie restriction, but the physiological consequences of SCH9 deletion are poorly understood. By transcriptional profiling of an sch9Delta mutant, we show that mitochondrial electron transport chain genes are upregulated. Accordingly, protein levels of electron transport chain subunits are increased and the oxygen consumption rate is enhanced in the sc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
77
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(83 citation statements)
references
References 43 publications
5
77
1
Order By: Relevance
“…High extracellular acetic acid levels and low pH together formed a toxic combination that accelerated yeast mortality in the post-mitotic environment and appeared to be largely responsible for many measured differences in yeast chronological lifespan, as reversing these effects reversed the lifespan differences. Relevant to this study, both tor1D and sch9D are reported to result in enhanced respiratory activity, possibly limiting acetic acid production by shunting fermentative products into respiratory metabolism [50,98]. Furthermore, the sch9D was found to be resistant to toxicity associated with high levels of acetic acid in a manner requiring RIM15 [110].…”
Section: Introductionsupporting
confidence: 53%
“…High extracellular acetic acid levels and low pH together formed a toxic combination that accelerated yeast mortality in the post-mitotic environment and appeared to be largely responsible for many measured differences in yeast chronological lifespan, as reversing these effects reversed the lifespan differences. Relevant to this study, both tor1D and sch9D are reported to result in enhanced respiratory activity, possibly limiting acetic acid production by shunting fermentative products into respiratory metabolism [50,98]. Furthermore, the sch9D was found to be resistant to toxicity associated with high levels of acetic acid in a manner requiring RIM15 [110].…”
Section: Introductionsupporting
confidence: 53%
“…Mitochondrial biogenesis and activity are controlled by the PKA, TOR, Sch9p, Snf1p, and Mec1p/Rad53p signaling pathways (11,(16)(17)(18)(19) and require several transcription factors, including Hap1p, Hap2/3/4/5p, Rtg1/ 3p, and Hcm1p (19)(20)(21)(22)76). Our results show that mitochondrial biogenesis and activity are also regulated by chromatin-mediated pathways.…”
Section: Discussionmentioning
confidence: 62%
“…The abundance and activity of mitochondria increase, and mitochondria enlarge during the diauxic shift (14,15). Mitochondrial biogenesis and activity are controlled by the protein kinase A (PKA), TOR, Sch9p, Snf1p, and Mec1p/Rad53p signaling pathways (11,(16)(17)(18)(19). The transition from fermentation to oxidative metabolism and the upregulation of mitochondrial biogenesis and activity require several transcription factors, including Hap2/3/4/5p, Cat8p, Rtg1/3p, and Hcm1p (19)(20)(21)(22)(23).…”
mentioning
confidence: 99%
“…Sch9 antagonizes Msn2/4 function and promotes the expression of genes encoding ribosomal proteins (23). Moreover, transcription of the genes encoding proteins important for mitochondrial function and mitochondrial ribosomal proteins is induced in sch9⌬ cells (14). Taken together, the behaviors of the genes observed in microarray analysis in 0 cells (21) could be attributed to the decreased Sch9 phosphorylation in 0 cells (Fig.…”
mentioning
confidence: 83%